Komposisi Flora dan Struktur Hutan Alami di Pulau Ternate, Maluku Utara - mirmanto, edi (Perhimpunan Biologi Indonesia, 2010)
ABSTRACTVegetation Analysis of Natural Forest in Ternate Island, North Maluku. A vegetation analysisof the Ternate natural forest has been conducted by establishing 9 plots of each 30-m x 30-m.All trees (dbh. eâ10 cm) within all plots were measured, their positions were determined, andtheir species were identified. In total there were 68 tree species recorded within plots belongingto 34 families. Trichospermum morotainense was the most common species, followed byAlbizia falcataria, Elmerilla ovata, Cordia mixa, and Macaranga longicaudatum. Almost allof the common species such as A. falcataria, Tristiopsis canarioides, Pometia pinnata, E.ovata and Intsia bijuga were found as emergent or canopy trees. According to the ordination(DCCA) analysis there were at least three tree species associations which were related tohabitat characteristics (conditions). However the populationâs dominant species varied amongsites, which might be related to the habitat characteristics and/or effects of human activities inthe past.Keywords: Vegetation, natural forest, Ternate, North Maluku